HUBUNGAN PENGETAHUAN IBU TENTANG MANFAAT SARAPAN DENGAN PERAN MENYIAPKAN MENU SARAPAN UNTUK ANAK SD - umi kalsum; edi purwanto (Poltekkes Kemenkes Kalimantan Timur, 2017)
ABSTRACT Background : School-age children are an invesment of nation because they are our next generation. One indicator of human resource quality is a good nutrition, the condition where the basic needs is fulfilled based on quality and quantity. For school-age children, eating breakfast is an important activity to increase the nutritional status beside lunch and dinner. By doing breakfast, they will have a lot of energy to perform some activities such as playing, studying and growing. Mother has an important role to prepare breakfast before the child goes to school. This research aimed to analyze the correlation between mother’s knowledge of the breakfast benefit and mother’s role in preparing breakfast for elementary school-age children. This research is a quantitative study, an analytical method, and a correlational design with cross sectional approach. The samples of this research are mothers of students in grade 1-3 in elementary schools within Sidodadi district of Samarinda that fulfill inclusion criteria. All the data is analyzed using chi square statistic. This research found that there is no correlation between mother’s knowledge and mother’s role in preparing breakfast for elementary school-age children with p=0,208 (p >0,05 ) Nevertheless, mothers are still suggested to prepare breakfast for their family especially children in elementary school, so they grow and develop healthily, brightly, and optimally. Writer also suggests to increase teachers’ role in motivating student to have breakfast before school. Keywords : Knowladge, Mothers role, Breakfast